Collaboration as a Capacity for Joint Action in Community-Based Cultural Heritage Tourism Management - Sentanu, I Gede Eko Putra Sri; Supriono, Supriono; Yustiari, Shinta Happy; Nirmalasandy, Fisca Mentari; Ferdiansyah, Muhammad Reynaldi; Aulia, Sarah Raudatul (Kolaborasi : Jurnal Administrasi Publik, 2025)
The research explores the dynamics of cultural heritage tourism management in Kayutangan, Malang City, within the context of the evolving creative economy, innovation, and localism in heritage revitalization. The study aims to describe and analyze stakeholder involvement, factors influencing collective action capacity, and strategies to enhance this capacity in managing cultural heritage tourism. Adopting an interpretive social science approach within a constructivist paradigm, the research utilizes a case study methodology to investigate joint action capacity among community members, government officials, and private sectors. Findings reveal active collaboration among these stakeholders, with coordinated efforts spanning community groups, government bodies, sub-districts, villages, and private enterprises such as banks. This collaboration facilitates improved management of cultural heritage tourism, albeit challenged by limited human resources, low community participation, and conflicts stemming from miscommunication and differing perspectives. The study concludes that sustained and enhanced collaborative governance is vital for the participatory management and sustainable development of heritage tourism in Kayutangan. Strengthening stakeholder relationships and communication channels emerges as a key strategy to overcome existing barriers and support collective welfare through cultural tourism initiatives.